2018
DOI: 10.1016/j.ultsonch.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficient room temperature synthesis of cardanol-based novolac resin using acoustic cavitation

Abstract: The present study deals with synthesis of cardanol-cased novolac (CBN) resin by the condensation reaction between cardanol and formaldehyde using acoustic cavitation. It is a step-growth polymerization which occurs in the presence of an acid catalyst such as adipic acid, citric acid, oxalic acid, sulphuric acid and hydrochloric acid. CBN was also synthesised by a conventional method for the sake of comparison of techniques. The effect of molar ratio, effect of catalyst, effect of different catalyst and effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Jadhav et al adopted a rare synthetic route to prepare cardanol based novolac resin. An energy efficient and time-saving ultrasound-facilitated synthesis method was utilized for preparing novolac resin, resulting in a reduction of reaction time from 5 h to 30 min compared to the conventional synthesis [ 109 ]. To improve the properties of the cardanol-formaldehyde resin, it was modified by substituting formaldehyde with furfural.…”
Section: Phenol Substitutes For Pf Resinmentioning
confidence: 99%
“…Jadhav et al adopted a rare synthetic route to prepare cardanol based novolac resin. An energy efficient and time-saving ultrasound-facilitated synthesis method was utilized for preparing novolac resin, resulting in a reduction of reaction time from 5 h to 30 min compared to the conventional synthesis [ 109 ]. To improve the properties of the cardanol-formaldehyde resin, it was modified by substituting formaldehyde with furfural.…”
Section: Phenol Substitutes For Pf Resinmentioning
confidence: 99%
“…The thermal performance of the prepolymer under an inert atmosphere was also evaluated, where the material remained stable up to 232°C, comparable to initial degradation temperatures of uncured phenolic resin 18 …”
Section: Resultsmentioning
confidence: 94%
“…The thermal performance of the prepolymer under an inert atmosphere was also evaluated, where the material remained stable up to 232 C, comparable to initial degradation temperatures of uncured phenolic resin. 18 Decomposition occurred in two main stages. The first stage of decomposition is observed between 232 and 402 C, where, approximately 36% of mass loss is observed.…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis has shown that supercavitation is the most promising technique for treatment of washing fluids [12][13][14]. Supercavitation occurs when axisymmetric bodies are flowed around by liquid [15][16][17]. The operating principle of SC-mechanisms is that flow slipping around the cavitator results in the formation of super-cavities that close directly in the flow, far away from the working surface of the machine [18,19].…”
Section: Fig 1 Scheme Of a Venturi Tubementioning
confidence: 99%